Fullerene nanopottery : shaping and interconnecting hollow nanostructures - Han, Fei (Nanyang Technological University, 2020)
My work has been largely focused on developing a methodology to fabricate fullerene hollow nanostructures, namely, nanopottery. It is a method to build, expand, and connect hollow compartments via a stepwise liquid templating strategy. Hollow nanostructures have been extensively used in materials, chemistry, and medicine. However, it is synthetically extremely difficult to increase their structural complexity. We bring pottery, the simplest and oldest method of making hollow structures, to the nanoscale, for the design and stepwise synthesis of hollow nanostructures. As the first step, in chapter 2, we established a three-solvents system: IPA, xylene, and DMF, for the controllable deposition of fullerene materials. Metal@fullerene core-shell nanoparticles were synthesized and studied as a model system. In the following chapter 3 and 4, we demonstrated that in the above system, the liquid nature of m-xylene droplets template can be exploited to the synthesis of fullerene hollow nanostructures with tailored shapes, for example, bowl, bottle, and cucurbit, etc. The liquid templates permit stepwise and versatile manipulation, which would lead to modular assembly of hollow nodes and junctions into interconnected hollow system. Such stepwise shaping, addition, and connection are the fundamental operations in pottery, which could greatly expand the synthetic freedom for designing complex hollow nanostructures and interconnected systems. Last but not least, we provided critical regio-selectivity for this system in chapter 5. With the precise controlling of the nanobowls’ opening size, the exposed area of droplet template can be precisely controlled to govern the extent of nanobowl self-assembly. A larger exposed area would allow more nanobowls to be assembled, so that steric hindrance as in organic chemistry was created among the bowls. In short, my work demonstrates the dexterity in manipulating liquid droplets for templating fullerene hollow structures. Importantly, through the studying of its underlying mechanism, it also opens a window for the synthesis of complex hollow systems with the soft templates. In comparison to the literature works, our understanding of the mechanism allows rational design of the structures, and further using the geometrical shapes of the hollow structures to create regio-selectivity. The knowledge of creating critical selectivity around the droplets as synthetic handles, and adding appropriate material at the appropriate time point is critical for elevating the synthetic freedom in a complex system (beyond simple and conventional).